Foreign influence on carbon disclosure: Evidence from Indonesian non-financial firms - Indah Fajarini Sri Wahyuningrum; Fitrarena Widhi Rizkyana; Muhammad Ihlashul Amal; Laela Dwi Elviana (Journal of Open Innovation: Technology, Market and Complexity)
This study investigates the extent of carbon emission disclosure practices among Indonesian firms and examines the key factors influencing Carbon Emission Disclosure. The research analyzes all non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2022, focusing on variables such as the presence of foreign board members, foreign investors, foreign listing status, and the educational background of board members to assess their association with carbon emission disclosure. Using purposive sampling, the study selects 695 observations for empirical analysis. Statistical methods, including multiple linear regression and descriptive statistics, are employed using STATA to evaluate the relationships. The findings reveal that carbon emission disclosure among Indonesian non-financial firms remains limited, with an average disclosure rate of only 23 %. Notably, the presence of foreign board members has a positive and statistically significant effect on carbon emission disclosure. In contrast, foreign investors and foreign listing status do not exhibit a significant influence. Surprisingly, the educational background of board members has a significant negative effect on disclosure levels, suggesting that higher education does not necessarily translate into greater environmental transparency. A novel contribution of this study is a comprehensive examination of foreign involvement in relation to carbon emission disclosures, an underexplored area in existing literature. The findings contribute to academic discourse on corporate environmental reporting and provide practical recommendations, particularly for policymakers, to strengthen regulatory frameworks mandating carbon emission disclosures in Indonesia.